The influence of learners socioeconomic habitat on academic performance: a case of selected primary schools in Vhembe East District, Limpopo Province, South Africa - Tshisikhawe, Tshifaro Plantina (My University, 2026)
The socioeconomic habitat of learners play a pivotal role in shaping their academic performance, especially in the early educational stages. The study's aim was to explore the influence of learners’ socioeconomic habitat on academic performance The research focused on key socioeconomic factors, such as household income, parental education levels, employment status, access to educational resources, and living conditions. The ecological systems theory underpinned the study, employing the interpretivist paradigm with an ethnographic research design. Purposive sampling was used to select participants from two primary schools, and the sample comprised 58 participants (2 principals, 2 departmental heads (DHs), 2 register teachers, 2 subject teachers, 40 learners, and 10 parents). Data was collected through face to face and focus group interviews and observations, and the collected data was analysed thematically, through coding. The main findings revealed that learners from low SES backgrounds faced multiple, interrelated challenges that negatively affect their academic engagement and performance. Learners from low SES lacked adequate parental academic and learning material support due to low educational and financial constraints, limiting access to essential learning resources. The study further revealed that educated parents provided academic support and recognised that education is a shared responsibility involving parents, learners, and teachers, and that collaboration among these three stakeholders is essential for effective learning. The findings also revealed a lack of essential facilities, such as adequate classrooms, libraries, halls, laboratories, and playgrounds, limiting both academic and extra-curricular development at the study sites. However, findings revealed that Saturday classes, after-school care or drop-centres could help learners from low SES to improve academically. The study recommends that events like parents’ day, fun days, casual days, sports days and career days should be introduced for learners to enjoy being at school. During these events, learners from low SES can socialise and play together with others to build their self-esteem and learn more effectively. Based on the main findings, the study further recommends that the government and school authorities should develop policies that foster parental involvement in their children’s education, and provide adequate infrastructure, such as classrooms, libraries, playgrounds, and technological equipment for schools, so that learners from low-income backgrounds can also academically benefit from the rich school environment.
M.A. in Sociology of Education
Department of Educational Studies
Keywords: Habitat; Low income; UCTD; Political involvement; Policymakers; Socioeconomic